The influence of different commercial hybrid rootstocks on the growth and development of seedless watermelon hybrid Kidman F1 in the conditions of the Left Bank Forest Steppe of Ukraine - Yarovy, G.; Galaguria, A. (Scientific Progress & Innovations, 2022)
The article presents the results of the influence of different commercial rootstock hybrids on the growth, development, and productivity of seedless watermelon hybrid Kidman F1 in the conditions of the Left-Bank Forest-Steppe of Ukraine. In 2019–2021, the influence of two hybrids of rootstocks Pelops F1 and Cobalt F1 on seedless watermelon hybrid Kidman F1, which formed various phenological and biometric parameters of plants, and had an impact on yield, was investigated. The grafted plants differed from ungrafted plants by phenological phases of development, so, on the rootstock Pelops F1, the duration of the period from planting seedlings of grafted watermelon to fruit ripening is 64–65 days, which is 4–5 days earlier than the control. The grafted plants on the rootstock Cobalt F1 had no significant difference from the control plants in the phenological phases of development. Biometric measurements for three years of observations allowed us to establish a significant difference between grafted and ungrafted seedless watermelon plants. Vaccination provided a significantly greater vegetative mass of plants. There were 184 more leaves on the Cobalt F1 rootstock and 131 more leaves on the Pelops F1 rootstock than in the control plants. In grafted plants, the length of the main stem significantly exceeded the control plants, so, on the rootstock Cobalt F1 by 139.0 cm longer, and on the rootstock Pelops F1 by 119.0 cm, respectively. The largest number of shoots of the first and second order was in the grafted plants, so, on the rootstock Cobalt F1, 16 pieces more, and on the rootstock Pelops F1 12 pieces more than in the control. For three years of testing on grafted plants, both early and total yields were higher. The highest yield of 62.5 t/ha was obtained when growing watermelon hybrid Kidman F1, grafted on the rootstock Cobalt F1, which is 24.1 t/ha higher than the control, and on the rootstock Pelops F1 53.5 t/ha, which is 15.1 t/ha higher than the control. Studies conducted in the conditions of the Left-Bank Forest-Steppe of Ukraine indicate the feasibility of using two rootstocks – hybrid Pelops F1, and hybrid Cobalt F1, in the cultivation of seedless watermelon. Thanks to grafting, the yield significantly increases relative to the control both in obtaining early production by 28–46 % and the total yield by 39–63 %, respectively. For three years of testing, there is a difference between the rootstocks themselves, so, the rootstock Cobalt F1 received a 9.0 t/ha higher yield compared to the rootstock Pelops F1. The expediency of using grafted plants in modern growing conditions is proven.